The music of Alejandro Núñez Allauca - Cuentas Peralta, Marco Sadiel (2023)
This article explores the influence and contribution of Peruvian composer Alejandro Núñez Allauca to his country's contemporary music during the second half of the 20th century. Núñez Allauca, a musician from the 60s and 70s generation, began his career as an accordionist before studying cello andcomposition, exploring a wide range of styles, from tonal music with Andean folklore elements to electronic and concrete music.Three of his works are briefly analyzed: Gravitación Humana (1970), which combines electronic sounds and concrete music; Moto ornamentale e perpetuo (1970), a piano piece that reflects his experience as an accordion soloist; and Sonrisa de Jesús (1999), a work with a religious theme that incorporates rhythms and scales of Andean music.Despite his talent and versatility, Núñez Allauca has not received adequate recognition in Peru, his music rarely performed and his scores are not commonly used in musicians' training. It is suggested that this may be due to various historical, social, and cultural factors, and arguments are offered to support the importance of Núñez Allauca's legacy for contemporary Peruvian culture.